2023
DOI: 10.3389/fnagi.2023.1096417
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Tai Chi on lower limb function of Parkinson’s disease patients: A systematic review and meta-analysis

Abstract: BackgroundAt present, the effect of Tai Chi (TC) on lower limb function in patients with Parkinson’s disease (PD) is controversial. Therefore, we conducted a meta-analysis on the influence of TC on lower limb function in PD patients.MethodsAccording to the PRISMA guidelines, seven databases were searched. Randomized controlled trials (RCTS) were selected and screened according to inclusion and exclusion criteria. We assessed the quality of the studies using the Cochrane Risk of Bias tool and then extracted the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…We found that Tai Chi, as an adjunctive therapy, had a positive impact on rehabilitating balance and mobility functions of the lower limbs in patients with Parkinson's disease. Our ndings align with previous studies, and the systematic reviews by Yu et al 2 and Zhu et al 21 have also a rmed the effectiveness of Tai Chi in improving balance and mobility functions in patients with Parkinson's disease. However, their research methods primarily compared Tai Chi with conventional medication.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We found that Tai Chi, as an adjunctive therapy, had a positive impact on rehabilitating balance and mobility functions of the lower limbs in patients with Parkinson's disease. Our ndings align with previous studies, and the systematic reviews by Yu et al 2 and Zhu et al 21 have also a rmed the effectiveness of Tai Chi in improving balance and mobility functions in patients with Parkinson's disease. However, their research methods primarily compared Tai Chi with conventional medication.…”
Section: Discussionsupporting
confidence: 92%
“…Tai Chi training emphasizes the constant shifting of the body's center of gravity between the two feet, facilitating the body's equilibrium by adjusting the support surface 39,40 . When compared to traditional exercise regimens, Tai Chi might yield superior advantages for individuals diagnosed with Parkinson's disease 41 . Tai Chi encompasses a variety of multidimensional exercises encompassing endurance, exibility, and neuromuscular coordination, along with numerous cognitive elements like body awareness, concentration, and meditation incorporated within its training 41,42 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TUG was used to assess balance and mobility in PD patients ( Zampieri et al, 2010 ). It has been suggested that an improvement in balance also represents to some extent an improvement in mobility ( Zhu et al, 2023 ). Therefore, this is one of the reasons why the sensitivity analysis yielded a positive result in terms of mobility.…”
Section: Discussionmentioning
confidence: 99%